2017
DOI: 10.31235/osf.io/kns57
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In-Home Firearm Access among US Adolescents and the Role of Religious Subculture: Results from a Nationally Representative Study

Abstract: Religious participation is linked to numerous positive safety outcomes for adolescents. Scant attention, however, has been paid to associations between religious participation and safety risks among adolescents. Using data from Add Health (N = 18,449), a nationally representative school-based sample of US adolescents, this study examines the relationship between adolescents’ religious affiliation and easy access to firearms at home. Regression analyses adjust for complex sampling design and compare easy firear… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 29 publications
(36 reference statements)
1
5
0
Order By: Relevance
“…Several studies asked youth whether they could easily gain access to household firearms, and have examined their behavioral correlates. The National Longitudinal Survey of Youth (Add Health) provided an important data source, generating at least six studies (Cretacci & Hendrix, ; Kim, ; Resnick et al., ; Ruback, Shaffer, & Chark, ; Stroope & Tom, ; Swahn, Hammig, & Ikeda, ). The first and second Add Health surveys included a specific question, “Is a gun easily available to you in your home?”, administered to 20,000 high school students in 1995.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies asked youth whether they could easily gain access to household firearms, and have examined their behavioral correlates. The National Longitudinal Survey of Youth (Add Health) provided an important data source, generating at least six studies (Cretacci & Hendrix, ; Kim, ; Resnick et al., ; Ruback, Shaffer, & Chark, ; Stroope & Tom, ; Swahn, Hammig, & Ikeda, ). The first and second Add Health surveys included a specific question, “Is a gun easily available to you in your home?”, administered to 20,000 high school students in 1995.…”
mentioning
confidence: 99%
“…The Add Health youth data revealed that easy access to firearms: increased youth's risks of violent offending and being a victim of violence (Ruback et al., ); was associated with higher youth suicidal thoughts, attempts and violence (Resnick et al., ), was often accompanied by easy access to alcohol and problems of alcohol misuse and was also associated with several distinctive demographic factors (Swahn et al., ); Conservative Protestants were disproportionally overrepresented among those with easy access to guns (Stroope & Tom, ); and they were more likely to become gun owners when they reached their early twenties (Cretacci & Hendrix, ). Findings from these studies suggest that youth's easy access to firearms is a distinctive cultural element associated with other behaviors that together may also be linked with premature mortalities.…”
mentioning
confidence: 99%
“…Stroope and Tom (2017) argue that an emphasis on "rugged masculinity" and religious legitimation for the Second Amendment also contribute to a link between evangelical Protestants and guns. This is not to suggest that other Americans do not also possess these cultural tools.…”
Section: Discussionmentioning
confidence: 99%
“…Using GSS data, the author finds that Protestants score higher than others on two separate indexes of individualism, while Protestant affiliation and individualism are both predictive of gun ownership and opposition to a gun permit requirement. Stroope and Tom (2017) point to still more factors that could explain the link between evangelical Protestants and guns. A cultural emphasis on masculinity and traditional gender roles could positively incline adherents toward gun ownership, informed by the position that a man's responsibility is the protection of others, particularly family.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation